Six fractions weekly as accelerated fraction radiotherapy: Is it applicable for nasopharyngeal cancer? A review - Widikusumo, Arundito; Purnamawati, Schandra (Contemporary Oncology/Współczesna Onkologia, 2019)
Standard therapy for nasopharyngeal cancer (NPC) is concurrent chemoradiation. Nevertheless, therapeutic outcomes are often unsatisfactory particularly for locally advanced stage. To enhance the therapeutic outcome, we may consider using altered fraction radiotherapy. Altered fraction radiotherapy is divided into two large groups for the therapy of NPC: hyperfraction radiotherapy and accelerated fraction radiotherapy. One of the accelerated fraction regimens suitable for NPC therapy is an accelerated regimen of six radiotherapy fractions weekly. This regimen is considered safe whether using conventional 2D planning technique or advance technique. Response to radiotherapy is better owing to the decrease in overall treatment time (OTT). Furthermore, acute or late side effects for this therapy are not very different to those of standard therapy. The conclusion is that we recommend the use of an accelerated regimen of six radiotherapy fractions weekly for locally advanced stage NPC with contraindication to concurrent chemoradiation, due to the high degree of clinical outcome as well as better tolerated side effect for NPC patients, particularly for those with locally advanced stage NPC.